Geochemical Characterization of Spring Waters in the Crati River Basin, Calabria (Southern Italy) - Simona Gaglioti; Ernesto Infusino; Tommaso Caloiero; Giovanni Callegari; Ilaria Guagliardi (Geofluids)
The characterization of the spatial variation of geochemical parameters in spring waters, especially the ones used for drinking purpose, is essential to identify potential risks to humans. In this work, results of a qualitative analysis on 190 samples of spring waters collected in the largest catchment of the Calabria region (southern Italy) are shown. Several physical and chemical parameters were analysed and the Langelier-Ludwig diagram was built to evaluate the hydrochemical facies of the sampled waters. Additionally, the relationships between water temperature and altitude and electric conductivity (EC) and altitude were assessed. Geostatistical methods were used to map the physical and chemical parameters. Results showed a good quality status of the spring waters in the Crati basin, with a predominant Ca-Mg-type hydrochemical facies. Then, a connection between EC and temperature with elevation has been detected in some area of the basin. Finally, the spatial analysis allowed identifying the distribution of the concentration of the several parameters.